High‐Temperature Operating Non‐volatile Memory of Printable Single‐Wall Carbon Nanotubes Self‐Assembled with a Conjugate Block Copolymer. Issue 6 (2nd November 2012) - Hwang, Sun Kak; Choi, Jae Ryung; Bae, Insung; Hwang, Ihn; Cho, Suk Man; Huh, June; Park, Cheolmin
<x xml:space="preserve">Abstract</x> Printable non‐volatile polymer memories are fabricated with solution‐processed nanocomposite films of poly(styrene‐block‐paraphenylene) (PS‐b‐PPP) and single‐wall carbon nanotubes (SWNTs). The devices show stable data retention at high temperatures of up to 100 °C without significant performance degradation due to the strong, non‐destructive, and isomorphic π–π interactions between the SWNTs and PPP block. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>